1984
DOI: 10.1159/000194691
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Pulmonary Functions after Reinflation in Chronic Atelectasis

Abstract: Recovery of the lungs after the reinflation of chronic atelectasis was studied experimentally using adult dogs. Obstructive absorption atelectasis was induced by banding the left main bronchus with a thin metallic plate. Tests were conducted 1 month after reinflation of the lungs. In the group of dogs which had suffered atelectasis for 3 months, static compliance and pulmonary blood flow were decreased by half at 1 month after reinflation; the conditions of reduced Po2, increased A-aDo2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Similarly, Ferrante et al made Yorkshire pig's right main stem bronchus plugging through a Fogarty‐catheter occlusion balloon inflation, and described atelectasis and its reexpansion using MRI in a few minutes. Harada et al established a dog model of pulmonary reexpansion after atelectasis by two thoracotomes and found that the pulmonary function of dogs within 1 month of atelectasis was restored to normal levels. However, the unilateral atelectasis in Harada's animal model, obtained by an aluminum plate flat pressing and sealing, was not suitable for simulating airway FB blockage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ferrante et al made Yorkshire pig's right main stem bronchus plugging through a Fogarty‐catheter occlusion balloon inflation, and described atelectasis and its reexpansion using MRI in a few minutes. Harada et al established a dog model of pulmonary reexpansion after atelectasis by two thoracotomes and found that the pulmonary function of dogs within 1 month of atelectasis was restored to normal levels. However, the unilateral atelectasis in Harada's animal model, obtained by an aluminum plate flat pressing and sealing, was not suitable for simulating airway FB blockage.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, as the pneumothorax and the lung collapse worsen, ventilation is also impaired. Removal of the pleural air pocket will resolve the pneumothorax and should return normal pulmonary function (Harada et al. 1984; Padrid 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The TLC can diminish with chronic pulmonary changes during pneumothorax. When the pneumothorax was resolved and the lung expanded the FRC and dead space increased providing little room for a normal tidal volume (Harada et al. 1984; Morris et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The re-expansion of the collapsed lung in pneumothorax causes pulmonary edema and increases the amount of superoxide radicals [4]. Blood delivery to the collapsed lung significantly decreases and the decrease lasts longer than expected because of the hypoxic vasoconstriction [2]. The absence of alveolar ventilation during collapse leads to resorption of the air and consumption of the oxygen by alveolar endothelial and epithelial cells.…”
Section: Introductionmentioning
confidence: 99%